Approach to Diarrhea in HIV Patients: Narrative Literature Review and Diagnostic Proposal (2025)
ABSTRACT: Diarrhea in patients infected with the human immunodeficiency virus (HIV) represents a challenge for the clinician. Its differential diagnosis includes infectious causes (bacteria, viruses, fungi, and parasites) as well as non-infectious ones. Among the infectious causes are microorganisms that can affect both immunocompetent and immunocompromised hosts, making the differential diagnosis broad. The presentation can be acute or chronic, with the latter having a greater impact on morbidity and quality of life for patients. The diagnostic approach should be sequential, first with non-invasive laboratory methods, progressing to endoscopic studies with biopsy in those individuals for whom reaching a diagnosis is difficult.